Meningitis what precaution is needed for central neuraxial blockade (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
DOI: http://dx.doi.org/10.3329/jbsa.v22i1.18083Journal of BSA, 2009; 22(1): 5-11